PENGARUH ARUS KAS OPERASI DAN LABA AKUNTANSI TERHADAP RETURN SAHAM PADA PERUSAHAAN KONSTRUKSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2024 - Syifa Khairunnisa; Safrudin; Karsam (Universitas La Tansa Mashiro, 2025)
This study aims to examine the influence of operating cash flow and accounting profit on stock returns in construction companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. Using a quantitative associative approach, this study employs secondary data from financial statements and annual stock prices. The sample consists of 8 companies, totaling 48 observations, selected through purposive sampling. The data were analyzed using multiple linear regression with SPSS version 23. The results show that operating cash flow has no significant effect on stock returns, while accounting profit has a significant positive effect. Simultaneously, both variables significantly affect stock returns with an Adjusted R² value of 0.122, indicating that 12.2% of the variation in stock returns can be explained by operating cash flow and accounting profit.